UJI DAYA TERIMA DAN NILAI GIZI MI BASAH YANG DIMODIFIKASI DENGAN TEMPE DAN WORTEL (Daucus carota L.) - Yohana Tetty Gultom; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Noodle is one of the most popular foodstaple in the community. Nowdays, the noodle was made as a replacement food of other staple foods such as rice. Generally, raw material of noodle is flour. However, the flour can also be modified with other foods such as tempe and carrot. Based on its nutrient composition, tempe and carrot are potential as a source of nutrition, which contains proteins, fat, calcium, phosphorus, iron, vitamin A, tiamin , vitamin C, riboflavin, niasin and fiber. The purpose of this research is to know the nutrient content and acceptability from the noodle with addition of tempe and carrot. This research is a research experiment making wet noodle with addition of  tempe and carrot by comparison (30% : 20%, 25% : 25%, 20% : 30%). Panelists in this study are university students of public healty in University North Sumatera , as many as thirty peoples. Acceptance of test data was analyzed by anova test and double Duncan test, and nutrient content is determined by using DKBM. The parameters analyzed  include the lucrative nature of the organoleptic color, aroma, taste and texture of wet noodle. The results of this research showed that the organoleptic test of color, flavor, taste, and texture are the most preferred panelist is wet noodle by addition of 25% tempe and 25% carrot. Based on the analysis of varians, the addition of tempe and carrot in different concentration on the creation of a wet noodle gave different effects of calor, flavor, taste, texture of a wet noodle. It is suggested for consumer to make wet noodles with addition of tempe and carrot  as an alternative food for rice. In addition, it is necessary to implement other foods diversification by added tempe and carrot to enrich  nutrient food. Keywords : wet noodle, tempe, carrot, organoleptic test, nutrient content